2013
DOI: 10.4103/0970-9185.105810
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative fasting in children: An audit and its implications in a tertiary care hospital

Abstract: Background:Prolonged preoperative fasting in children is a common problem, especially in highvolume centers. All international professional society guidelines for preoperative fasting recommend 2 h for clear fluids, 4 h for breast milk and 6 h for solids, nonhuman and formula milk in children. These guidelines are rarely adhered to in practice.Aims:An audit was undertaken to determine the length of preoperative fasting time in children and its causes.Settings and Design:Cross-sectional study of 50 children bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 11 publications
3
36
0
2
Order By: Relevance
“…In another recent study, the authors even suggested that parents may deliberately misrepresent the actual fasting status of their child [17]. However, it is important to note that parental noncompliance with preoperative fasting guidelines may be caused by lack of understanding or incorrect orders of medical staff [18].…”
Section: Parental Noncompliancementioning
confidence: 97%
“…In another recent study, the authors even suggested that parents may deliberately misrepresent the actual fasting status of their child [17]. However, it is important to note that parental noncompliance with preoperative fasting guidelines may be caused by lack of understanding or incorrect orders of medical staff [18].…”
Section: Parental Noncompliancementioning
confidence: 97%
“…Therefore, the order NPO starting at midnight for elective surgery can be adjusted to no intake of solid food and milk products 6 h before surgery and fast from clear fluid 2 h before surgery [410]. …”
Section: Introductionmentioning
confidence: 99%
“…9,10 The MFT at Queen Elizabeth Central Hospital was too long in each of the clinical audits conducted over the last 5 years. Reasons mentioned for long fasting times in the developed world -nurses still order "nil by mouth after midnight", that they dealt with an outpatient population 3 or that obviously wrong information was given to secure timely flexibility for the theatre 18 were not typical for our hospital. Children being starved of water for a mean of 8.5 hours, as at our institution, exceeds the recommendations of all international guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Nevertheless, prolonged periods of preoperative fasting are still reported. [3][4][5][6] Data for resource-poor African countries are scarce, 7,8 and long-term audits are lacking. At Queen Elizabeth Central Hospital, which is the largest hospital in Malawi, we identified that preoperative starving times were longer than the standards set by the anesthetic department.…”
Section: Introductionmentioning
confidence: 99%